2003
DOI: 10.1124/jpet.103.058321
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Promoted Colon Cancer Growth via Epidermal Growth Factor Receptor, c-Src, and 5-Lipoxygenase-Mediated Signal Pathway

Abstract: Nicotine [3-(1-methyl-2-pyrrolidinyl)-pyridine], a major alkaloid in tobacco, has been implicated as playing a role in carcinogenesis. Our previous study showed that passive cigarette smoking promoted inflammation-associated colonic adenoma formation in mice, and 5-lipoxygenase (5-LOX) plays an important role in this process. In the present study, we aimed to investigate whether nicotine could stimulate colon cancer cell proliferation and tumor growth in nude mice xenograft model and the possible mechanisms in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 30 publications
4
44
1
1
Order By: Relevance
“…Patients carrying T allele at promoter region of CYP2J2 gene thus had lower median value of 14,15 EETs concentrations, which might protect their coronary vasculatures. In addition, smoking could alter the metabolites of arachidonic acid (Ye et al, 2004). This effect was observed, in our study, more significantly among CYP2J2 G-50T polymorphism carriers whom probably were more prone to the oxidative stress damage due to their impaired EETs functions.…”
Section: The Synergistic Effects Of the Cyp2j2 G-50t Genotype And Smosupporting
confidence: 55%
“…Patients carrying T allele at promoter region of CYP2J2 gene thus had lower median value of 14,15 EETs concentrations, which might protect their coronary vasculatures. In addition, smoking could alter the metabolites of arachidonic acid (Ye et al, 2004). This effect was observed, in our study, more significantly among CYP2J2 G-50T polymorphism carriers whom probably were more prone to the oxidative stress damage due to their impaired EETs functions.…”
Section: The Synergistic Effects Of the Cyp2j2 G-50t Genotype And Smosupporting
confidence: 55%
“…This methodology could led to a selection bias excluding deceased patients possibly with a worst prognosis. This point could represent the reason of the longer TTP and OS observed in our analysis when compared with that observed with the same cancer population in published clinical trials (9). On the contrary the observed response rate in the population of smokers vs. nonsmokers is reasonably reliable.…”
Section: Discussioncontrasting
confidence: 42%
“…Preclinical data revealed that 4-(N-Methyl-N-nitrosamino)-1-(3-pyridyl)-1-butanone (NNK), the tobacco-specific nitrosamine, was able to stimulate the proliferation of SW1116 colon cancer cell line enhancing NF-κB DNA binding activity (7). Moreover, nicotine, the major alcaloid in tobacco, increases the oxidative stress of colon cancer cells, leading to the activation of NF-κB, a redox-sensitive trascription factor (8) and promotes colon cancer cell proliferation and tumor growth in a dose-dependent manner, increasing EGFR phosphorylation levels (9).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor cell proliferation, angiogenesis, and local and distant cell migration are hallmarks of solid tumors. Our recent studies show that nicotine induces proliferation of human adenocarcinoma cells via a cyclooxygenase (COX)/lipoxygenase -dependent pathway to metabolize fatty acids into eicosanoids (4,5). The effects of COX-2 inhibitors on treatment and chemoprevention of gastric cancer have been widely reported (6,7).…”
Section: Introductionmentioning
confidence: 99%